Biology of Begonia sect. Wageneria (Klotzsch) A.DC. under cultivation conditions (ex situ) - Fershalova Tatiana (EDP Sciences, 2021)
Morphological structure, features of growth and development of Begonia species of the Wageneria section (B. convolvulacea, B. glabra, B. fagifolia) under ex situ conditions were studied. The architectural model and structure of inflorescences, as well as the dynamics of shoot growth and flowering, are established and described. Recommendations for the optimal cultivation of the Wageneria section begonias in greenhouses and rooms are presented. The main factor affecting the success of cultivation and decorative effect is the air temperature; the optimal one is +20-30 °C. Begonia convolvulacea and B. glabra proved to be the most resistant to various cultivation conditions.